2007
DOI: 10.1039/b711961e
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia IRMS-TPD measurements and DFT calculation on acidic hydroxyl groups in CHA-type zeolites

Abstract: Brønsted acidity of H-chabazite (CHA) zeolites (Si : Al(2) = 4.2) was investigated by means of ammonia infrared-mass spectrometry/temperature-programmed desorption (IRMS-TPD) methods and density functional calculations. Four IR bands were observed at 3644, 3616, 3575 and 3538 cm(-1), and they were ascribable to the acidic OH groups on four nonequivalent oxygen sites in the CHA structure. The absorption band at 3538 cm(-1) was attributed to the O(4)H in the 6-membered ring (MR), and ammonia adsorption energy (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 34 publications
9
39
0
Order By: Relevance
“…This shift corresponds to some calculations which also used plane wave approach 19,26 . Note however that we are not using the customary notation of scaling factor for computed frequencies, as a scaling factor is typically based on a full range (or a very limited number of sub-ranges) of vibrational frequencies of a target system 67 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 28 , although their computed HO3 vibration was significantly higher, 3538 cm -1 , than ours. For better visibility the computed HO3 bands were omitted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This shift corresponds to some calculations which also used plane wave approach 19,26 . Note however that we are not using the customary notation of scaling factor for computed frequencies, as a scaling factor is typically based on a full range (or a very limited number of sub-ranges) of vibrational frequencies of a target system 67 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 28 , although their computed HO3 vibration was significantly higher, 3538 cm -1 , than ours. For better visibility the computed HO3 bands were omitted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Very precise analysis be comes possible by obtaining not only the experimental observation but also the theoretical calculation. Our study using the DFT calculation was first applied to chabazite 14) . Chabazite has a simple structure with only one kind of T-site like Y zeolite, and therefore the structure unit consists of relatively small number of atoms.…”
Section: Dft Calculation To Support the Experimental Observationmentioning
confidence: 99%
“…[29,30] FTIR spectroscopy with probe molecules has been used in the determination of the number of acid sites for cation modified ZSM-5. [33][34][35] Niwa and co-workers reported that IR combined with NH 3 -TPD simultaneously provides information on the strength and quantity of acid sites of zeolites [23,24,36,37] and ZrO 2 . [38] Studies that explore how the cations affect the acidity of ion-exchanged zeolites are rare.…”
Section: Introductionmentioning
confidence: 99%